The role of branding in the perceived success of Small and Medium Enterprises (SMEs) in South Africa - Makhuvha, Munzhedzi (My University, 2021)
Although branding in SMEs is starting to receive a significant interest from academic researchers, there is still limited studies that have considered or studied the relationship between branding and the success of Small and Medium Enterprises, particularly in South Africa. This qualitative study investigated the relative importance of branding in the perceived success of SMEs in South Africa, looking at SMEs in Gauteng and Limpopo. The reason behind a study of this nature was because of the major role that SMEs play in the development of the South African economy. Qualitative research is a methodology that produces underlying insights in exploratory research. The objectives of this study were to identify the awareness amongst SME owners when it comes to the importance of branding and to determine if branding does have an impact on the perceived success of these SMEs. When a company has a strong brand, it supports the business strategy and increases efficiency. A strong brand helps a company in driving long-term profitability. Rokhim, Mayasari and Wulandari (2021) indicated in their study that most of their respondents agreed that branding is a critical factor in supporting business performance. For a company to be able to stand out and keep its promise to the customers, a solid brand is a necessity. A lot of small businesses offer the same service and have similar products that offer similar benefits, so it is imperative for a company to create an exclusive identity which will make the company different from its competitors. The sampling technique that was used with this study was non-probability sampling, on a convenience basis. The sample size was 20 SMEs owners based in Gauteng and Limpopo. Data was analysed using thematic analysis. The study showed that most SMEs do understand what branding is and what it can do for their business. As much as some understand the importance of branding, they still have not fully engaged in the practice. Some businesses maintained that word of mouth can also do as much as branding, if not more, so they still practice word of mouth more than any other form of communication. Some of the SMEs also acknowledged that giving back to the community earns them more trust and loyal customers than any branding can do. It was also clear from the study that those who are engaged in branding are showing a higher success rate than those who are not. By creating a strong brand for their businesses, they have survived much longer than their competitors and also find it easier to expand as their brands are already known and trusted. They find that customers trust them more. This study has made recommendations for future researchers to carry out more studies on SME branding and the success thereof, focusing on multiple stakeholders and using different research approaches. Investigations need to be done on whether branding also impacts the customers purchase decisions. From the study, it was also clear that the South African government needs to play a more visible role in assisting SMEs, most importantly with financial support and having policies in place that makes it easier for SMEs to access big establishments looking for financial success
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Management (in Strategic Marketing), 2021
Keywords: Small and Medium Enterprises (SMEs; South Africa; SDG-8: Decent work and economic growth